Controlled-Release Oxycodone and Naloxone in the Treatment of Chronic Low Back Pain: A Placebo-Controlled, Randomized Study - C Cloutier; J Taliano; W O’Mahony; M Csanadi; G Cohen; I Sutton; D Sinclair; M Awde; S Henein; L Robinson; J Eisenhoffer; PS Piraino; et al. (Pain Research and Management)
BACKGROUND: For Canadian regulatory purposes, an analgesic study was required to complement previously completed, pivotal studies on bowel effects and analgesia associated with controlled-release (CR) oxycodone/CR naloxone.